Assessment of the Effectiveness of Communication Strategies and Processes in Project-Based Firms in South Africa - Paul Saah; Nelson Sizwe Madonsela (Logistic and Operation Management Research (LOMR), 2025)
In South Africa, project-based businesses frequently struggle to maintain effective communication, which is essential for managing stakeholders, organizing work, and accomplishing project objectives. To find weaknesses and suggest fixes for improved project performance, this study examines how well the communication methods of small business enterprises work. The current study evaluates the efficacy of communication practices and processes within project-based organizations. Using pertinent literature and conceptual analysis to offer insight and suggestions for change, this study employs a systematic review technique to investigate and address the issues surrounding communication practices and procedures within project-based organizations. Data from a diverse range of project-based businesses, encompassing various industries and sizes, was collected through document analysis.  The study found that effective communication is crucial for project-based firms because it helps to foster collaboration, ensure goal clarity, enhance stakeholder engagement, and mitigate risks, which eventually leads to project success and organizational effectiveness. By analyzing the distinctive efficacy of communication tactics and procedures in project-oriented businesses in South Africa, this study offers context-specific insights that are frequently overlooked in international research. To improve project outcomes and successfully handle context-specific difficulties, the study recommends that project-oriented businesses in South Africa use customized communication strategies that place a high priority on clarity, stakeholder participation, and adaptation.